Predicting Marital Adjustment by Psychological Flexibility and Frustration Discomfort - Alizadeh, Zahra; Dokaneifard, Farideh; Fattahi Andabil, Azam (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to investigate the predictive roles of psychological flexibility and frustration discomfort on marital adjustment among married women. Specifically, it sought to assess how these psychological constructs influence marital satisfaction and cohesion.Methods and Materials: A cross-sectional design was employed, sampling 350 married women from various counseling centers in Tehran in 2023. Participants completed standardized questionnaires measuring marital adjustment (Dyadic Adjustment Scale), psychological flexibility (Acceptance and Action Questionnaire – II), and frustration discomfort (Frustration Discomfort Scale). Multiple linear regression analyses were conducted using SPSS version 27 to explore the predictive value of psychological flexibility and frustration discomfort on marital adjustment, adjusting for potential confounders such as age and gender.Findings: The results revealed that both psychological flexibility (β = 0.25, p < 0.01) and frustration discomfort (β = 0.29, p < 0.01) significantly predicted marital adjustment, accounting for 42% of the variance in marital adjustment scores. These findings indicate that higher levels of psychological flexibility and lower levels of frustration discomfort are associated with better marital satisfaction and cohesion.Conclusion: The study underscores the importance of psychological flexibility and frustration discomfort in influencing marital adjustment. It suggests that interventions aimed at enhancing psychological flexibility and reducing frustration discomfort may contribute to improving marital satisfaction and stability. These findings highlight the need for a holistic approach in marital counseling and therapy that considers these psychological constructs.